Challenging the Sovereign: Three Types of Early Modern Federal Theory - Smolenski, Jan (Politik, 2016)
In this paper, I develop three ideal types of early modern federal theories: sovereignty relativizing federalism, sovereignty pooling federalism, and bottom-up federalism. Each of these types respond to a different political effect of the development of the modern state: organ sovereignty, hostile geopolitical environment, and disempowerment of the society as a corollary to organ sovereignty, respectively. Each of these types conceives of the federation as an alternative to the state. I compare and contrast these types along the lines of implementation of the federal principle of self- and shared rule, the criteria of evaluation of federal arrangements, and the normative implications.